Holm Oak (Quercus ilex L.) canopy as interceptor of airborne trace elements and their accumulation in the litter and topsoil - Fantozzi, Federica; Monaci, Fabrizio; Blanusa, Tijana; Bargagli, Roberto (ENVIRONMENTAL POLLUTION, 2013)
We investigated the role of urban Holm Oak (Quercus ilex L.) trees as an airborne metal accumulators and metals' environmental fate. Analyses confirmed Pb, Cd, Cu and Zn as a main contaminants in Siena's urban environment; only Pb concentrations decreased significantly compared to earlier surveys. Additionally, we determined chemical composition of tree leaves, litter and topsoil (underneath/outside tree crown) in urban and extra-urban oak stands. Most notably, litter in urban samples collected outside the canopy had significantly lower concentrations of organic matter and higher concentrations of Pb, Cu, Cd and Zn than litter collected underneath the canopy. There was a greater metals' accumulation in topsoil, in samples collected under the tree canopy and especially near the trunk ('stemflow area'). Thus, in urban ecosystems the Holm Oak stands likely increase the soil capability to bind metals. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND publisher: ELSEVIER SCI LTD
Keywords: Airborne metals; leaves; Leaves litter; Quercus ilex; Topsoil; Urban environment

Effect of elevated CO2 on carbon partitioning in young Quercus ilex L. during resprouting - Aranjuelo, Iker; Pintó-Marijuan, Marta; Avice, Jean Christophe; Fleck, Isabel (Rapid Communications in Mass Spectrometry, 2011)
Stored carbon (C) represents a very important C pool with residence times of years to decades in tree organic matter. With the objective of understanding C assimilation, partitioning and remobilization in 2-year-old Quercus ilex L., those trees were exposed for 7 months to different [CO2] (elevated: 700 µmol mol−1; and ambient: 350 µmol mol−1 CO2). The 13C-isotopic composition of the ambient CO2 (ca. −12.8‰) was modified (to ca. −19.2‰) under the elevated CO2 conditions in order to analyze C allocation and partitioning before aerial biomass excision, and during the following regrowth (resprouting). Although after 7 months of growth under elevated [CO2], Q. ilex plants increased dry matter production, the absence of significant differences in photosynthetic activity suggests that such an increase was lower than expected. Nitrogen availability was not involved in photosynthetic acclimation. The removal of aboveground organs did not enable the balance between C availability and C requirements to be achieved. The isotopic characterization revealed that before the cutting, C partitioning to the stem (main C sink) prevented leaf C accumulation. During regrowth the roots were the organ with more of the labelled C. Furthermore, developing leaves had more C sink strength than shoots during this period. After the cutting, the amount of C delivered from the root to the development of aboveground organs exceeded the requirements of leaves, with the consequent carbohydrate accumulation. These findings demonstrate that, despite having a new C sink, the responsiveness of those resprouts under elevated [CO2] conditions will be strongly conditioned by the plant's capacity to use the extra C present in leaves through its allocation to other organs (roots) and processes (respiration). Copyright © 2011 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd
Keywords: carbon allocation; Cutting; Elevated CO2; leaves; Photosynthetic activity (voyant); Regrowth; roots

Transfer of 238U, 230Th, 226Ra, and 210Pb from soils to tree and shrub species in a Mediterranean area. - Blanco Rodríguez, P.; Vera Tomé, F.; Lozano, J. C.; Pérez Fernández, M. a (Applied radiation and isotopes : including data, instrumentation and methods for use in agriculture, industry and medicine, 2010)
The soil-to-plant transfer factors of natural uranium isotopes ((238)U and (234)U), (230)Th, (226)Ra, and (210)Pb were studied in a disused uranium mine located in the Extremadura region in the south-west of Spain. The plant samples included trees (Quercus ilex, Quercus suber, and Eucalyptus cameldulensis) and one shrub (Cytisus multiflorus). All of them are characteristic of Mediterranean environments. The activity concentrations in leaves and fruit were determined for the tree species at different stages of growth. For the shrub, the total above-ground fraction was considered in three seasons. For old leaves and fruit, the highest activity concentrations were found in Eucalyptus cameldulensis for all the radionuclides studied, except in the case of (230)Th that presented similar activity concentrations in all of the tree species studied. In every case, the transfer to fruit was less than the transfer to leaves. In the shrub, the results depended on the season of sampling, with the highest value obtained in spring and the lowest in autumn. Important correlations were obtained for (238)U and (226)Ra between the activity ratio in soils with that in leaves or fruit.
The following values have no corresponding Zotero field: accession-num: 20153657
Keywords: Arboreal species; Fruit; leaves; Natural radionuclides; Soil-to-plant transfer factors

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: breakdown; colonisation; leaves; river; shredders

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: breakdown; colonisation; leaves; river; shredders

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V; Perrini, G; Tomasello, M (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V.; Perrini, G.; Tomasello, M. (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563doi: 10.1080/10406630213563The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F. (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

UV-band and acid rain effects on beach ( Fagus sylvatica L.) and holm oak ( Quercus ilex L.) leaves - Paoletti, E (Chemosphere, 1998)
Beech (Fagus sylvatica L.) and holm oak (Quercus ilex L) leaves were subjected to simulated acid rain and UV-B radiation for 10 days. The almost glabrous beech leaves revealed a greater predisposition to developing macroscopic necrotic lesions than the pubescent holm oak leaves. This response is due primarily to their different morpho-anatomical structure, rather than to a difference in the synthesis of UV-B absorbing pigments (flavonoids); the response was also accompanied by microscopically observable alterations (collapse of epidermal cells, fusion of surface wax structures, structural damage to the stomata) and by the reduction of stomatal conductance
Keywords: acid rain; beech; damage; Holm oak; leaves; necrosis; stomatal conductance (voyant); uv-b radiation

The aquatic processing of sclerophyllous and malacophyllous leaves on a Mediterranean island (Corsica) : spatial and temporal pattern - Schwarz, A E; Schwoerbel, J (Annales de Limnologie - International Journal of Limnology, 1997)
Leaves of two species, alder (Alnus glutinosa) and holm-oak (Quercus ilex), were exposed in bags of two mesh sizes in two climatically contrasting sites of a Corsican softwater stream. Leaves were incubated both in winter and in summer for about 6 months. The field experiment was designed to determine the influence of both spatial (climate) and temporal (season) variations of temperature, as well as differences in the chemical and physical properties of sclerophyilous and malacophyllous leaves, on leaf decomposition rates. Comparisons were made between leaves colonized by macroinvertebrates and leaves protected by finemesh. In winter and summer, holm-oak leaves were colonized much less by macroinvertebrates than alder leaves. Spatial and temporal differences in leaf litter processing were mainly dependent on three factors (i) the chemical and physical properties of the leaves, (ii) the abundance of macroinvertebrates in the sediment and (iii) the temperature. The climatical pattern of temperature had a greater influence than its seasonal pattern. In contrast with many other studies, abiotic factors dominated over biotic factors in this study.
Keywords: alnus glutinosa; decomposition; leaves; macroinvertebrates; Mediterranean ecosystem; Quercus ilex; Temperature

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F.; Ferretti, M.; COZZI, A. (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves

Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F; Ferretti, M; Cozzi, A (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves

Seasonal courses of photosynthetic activity and sublethal temperature tolerance of Quercus ilex leaves - Méthy, M; Trabaud, L (Forest Ecology and Management, 1993)
The reaction of the photosynthetic system of a sclerophyllous tree of the Mediterranean region (Quercus ilex) to three temperature levels (one ambient and two sublethal) was analysed monthly for 1 year. Measurements were carried out on leaves less than 3 months old as well as on leaves older than 3 months by laser-induced chlorophyll fluorescence. Treatments were: control (unheated), 50°C for 30 min, and 60°C 10 min. Both for unheated and treated leaves the vitality index shows a seasonal course depending on the treatments. At 50°C the photosynthetic apparatus of leaves of the two ages is moderately affected. At 60°C the apparatus is severely damaged whatever the season and is unable to recover. The consequences for the management of Q. ilex forests in relation to some thermal stresses are considered.
Keywords: chlorophyll fluorescence; leaves; photosynthetic apparatus; Quercus ilex (PG); thermal stress

SUCCESSION OF BACTERIA ATTACHED TO EVERGREEN OAK LEAF SURFACES - Périssol, C; Roux, M; LEPETIT, J (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
Heterotrophic attached bacteria were isolated from evergreen oak leaf surfaces (Quercus ilex L.) on both phylloplane and litter at each season during one year. Few epiphytic bacteria were recovered from the phylloplane (18 %) in comparison with the litter. The data derived from the 324 strains were subjected to cluster analysis. The taxonomic structure displayed 44 phenetic groups. The bacterial communities on leaf surfaces belonged mainly to two genera: Bacillus (31 %), present on both phylloplane and litter, and Pseudomonas (35 %) present only on the litter. Some communities of Bacillus were able to degrade structural chemical components of the leaf, such as pectins or lignin monomers. The Bacillus isolates were generally more numerous in spring and in summer, i.e. during the warm seasons, whereas Pseudomonas predominated in autumn and winter. In vitro measurements of strains growth rates showed moreover that Bacillus strains grew better at 40-degrees-C than Pseudomonas strains. A climate-related factor, namely temperature, has therefore a great influence on the natural selection process of these communities. Another seasonal succession was observed, involving two genera: Xanthomonas predominant in winter and Lactobacillus in summer, as well as the Enterobacteriaceae family in autumn.
Keywords: ATTACHED BACTERIA; leaves; litter; PHYLLOPLANE

Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal - Fernandes, J. C.; Henriques, F. S. (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.
Keywords: acorns; holm oak (voyant); leaves; Metal pollution

Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal - Fernandes, J C; Henriques, F S (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.
Keywords: acorns; holm oak (voyant); leaves; Metal pollution

Crecimiento longitudinal del alcornoque: segmentos y hojas - Caritat, A; Molinas, M; Oliva, M (SCIENTIA gerundensis, 1988)
This paper is directed to the basic understand of longitudinal growth of the cork-tree Quercus suber L. Branch constitution is analized through the relation of segments and leaves. To duly recognize segments in branches, an apropiate nomenclature is used. Segments length changes from 0,2 to 11,6 cm, with an average of 2,3 cm. Two kind of shoots, long and short shoots, can be distinguished. Segment elongation tend to decrease as succesive periods accumulate. No differences in segments can be related to the period of the year in which they were developed. Leaves show heteroblastic distribution. Leave lamina has an average length of 3,3 cm and is 2,O cm wide. Petiol is very constant with an average of 0,6 cm.
Keywords: branch growth; cork-tree; leaves; Quercus-suber; shoots

Free and bound hydroxyl and carboxyl groups in the cutin of Quercus suber leaves - Agulló, C; Collar, C; Seoane, E (Phytochemistry, 1984)
The number of free and bound hydroxyl and carboxyl groups of the cutin of Quercus suber leaves was investigated by the lithium borohydride hydrogenolysis of mesyl-cutin compared with the lithium borohydride hydrogenolysis of untreated cutin. Fifty per cent of the vic-diol groups of the trihydroxy C18 acid component and twenty five per cent of the secondary hydroxyl groups of the dihydroxy C16 acid component are free. The rest of the secondary and all of the primary hydroxyl groups are esterified; all carboxyl groups are esterified.
Keywords: cutin; Fagaceae; free hydroxyl groups; hydrogenolysis; leaves; mesyl-cutin; Quercus suber